S136 Fungal sputum culture in patients with severe asthma is associated with a reduced post bronchodilator FEV1. (16th November 2010) - Agbetile, J; Fairs, A; Bourne, M; Hargadon, B; Mutalithas, K; Monteiro, W; Edwards, R; Morley, J; Desai, D; Brightling, C E; Bradding, P H; Green, R H; et al.
Abstract : Introduction and objectives: IgE sensitisation to fungal allergens is common in severe asthma, but the clinical relevance of this, and the relationship to airway colonisation with fungi, is not known. Many of the fungi that can grow at body temperature are filamentous moulds from the genera Aspergillus and Pencillium . We report here the relationship between lung function and fungal sputum culture in patients with severe asthma. Methods: We recruited 126 patients attending a tertiary referral centre with a diagnosis of asthma and 18 healthy volunteers. 93% of patients were on GINA treatment step 4 or higher. At a single stable visit subjects underwent: spirometry with reversibility to 200 μg salbutamol; sputum fungal culture and a sputum cell differential count; skin prick testing to both common aeroallergens and an extended fungal panel (+ve ≥3 mm); specific IgE to Aspergillus fumigatus by CAP (positive >0.35 kU/l). Fungi were identified by morphology and species identity confirmed by sequencing regions of the nuclear ribosomal operon. Results: Patients had a mean age of 56 years (21–84 years); 48% were males with median ICS dose of 800 μg Fluticasone equivalent. 60% were atopic to common aeroallergens, 45% were IgE sensitised to one fungal allergen and 27% to ≥2 fungal allergens. 64% of patients cultured a mould in their sputum, 7% more than one species. This compared with three healthy subjects (17%) culturing any mould (p<0.01). Aspergillus species were most frequently cultured (n=58) followed by Penicillium species (n=15) and Thermoascus species (n=2), others (n=8). Four fungal genera were cultured from healthy volunteers sputum, - Aspergillus, Penicillium, Coprinus and one other. Post bronchodilator FEV1 % predicted was 71% in those with a positive fungal culture vs 84% in those who were culture negative, (p<0.01). There were no differences in the sputum cell differential between culture positive and negative patients. Conclusions: In addition to IgE fungal sensitisation, sputum culture focused towards detection of moulds is frequently positive and associated with impaired post-bronchodilator FEV1. Colonisation of the airways with mould in asthma could be responsible for the development of fixed airflow obstruction.